Macular Ganglion Cell Layer Thickness in Patients Using Oral Isotretinoin - Kocamis, Ozkan; Acer, Ersoy (Journal of Ophthalmic Science, 2017)
Objective: Determining the effects on macular ganglion cell layer thickness in patients using isotretinoin by utilization of optical coherence tomography. Material and Methods: Sixty eyes of 30 patients using isotretinoin and 60 eyes of 30 control group patients in the same age range were included in this study. The average age of the patients using isotretinoin was; 21.2 ± 3.62 years, whereas the average age of the patients in the control group was 22.7 ± 3.7 years. The thickness of the macular ganglion cell layer (GCL), the retinal nerve fiber layer (RNFL) and subfoveal macular thickness of all patients were measured with optical coherence tomography (OCT). Results: The macular ganglion cell layer thickness in the OCT of the patients using isotretinoin was measured as 61.6±4.6 µm, 62.4±4.4µm, for the right and left eye respectively, whereas the thickness in the control group was measured as 60.6±4.1µm, 61.2±4.9µm respectively. The retinal nerve fiber layer thickness in the OCT of the patients using isotretinoin was measured as 74.8±11.3µm, 76.2±12.3µm, for the right and left eye respectively, whereas the thickness in the control group was measured as 72.2±10.5µm, 74.1±1.9µm, respectively. Conclusions: No statistically significant difference was observed in the macular ganglion cell layer thickness, retinal nerve fiber layer thickness and macular thickness in terms of both the right and left eyes between the control group and patients using isotretinoin.
Keywords: Isotretinoin; Optical coherence tomography; Retinal nerve fiber layer; Ganglion cell layer; Macular thickness